Engineering Saccharomyces cerevisiae for next generation ethanol production. Issue 6 (8th April 2013) - den Haan, Riaan; Kroukamp, Heinrich; Mert, Marlin; Bloom, Marinda; Görgens, Johann F.; van Zyl, Willem H.
Abstract Conversion of cellulose, hemicellulose or starch to ethanol via a biological route requires enzymatic conversion of these substrates to monosaccharides that can be assimilated by a fermenting organism. Consolidation of these events in a single processing step via a cellulolytic or amylolytic microorganism(s) is a promising approach to low‐cost production of fuels and chemicals. One strategy for developing a microorganism capable of such consolidated bioprocessing (CBP) involves engineering Saccharomyces cerevisiae to expresses a heterologous enzyme system enabling (hemi)cellulose or starch utilization. The fundamental principle behind consolidated bioprocessing as a microbial phenomenon has been established through the successful expression of the major (hemi)cellulolytic and amylolytic activities in S. cerevisiae. Various strains of S. cerevisiae were subsequently enabled to grow on cellobiose, amorphous and crystalline cellulose, xylan and various forms of starch through the combined expression of these activities. Furthermore, host cell engineering and adaptive evolution have yielded strains with higher levels of secreted enzymes and greater resistance to fermentation inhibitors. These breakthroughs bring the application of CBP at commercial scale ever closer. This mini‐review discusses the current status of different aspects related to the engineering of S. cerevisiae for next generation ethanol production. © 2013 Society of Chemical Industry